POLA PEMBELAJARAN TAUHID DALAM PENGAMALAN TAREKAT TIJANIYAH DI PONDOK PESANTREN AL-MUHAJIRIN KOBA- BANGKA TENGAH - Ratna Dewi (Scientia: Jurnal Hasil Penelitian, 2022)
The Tijaniyah Order is a unique and controversial order. Owned This tarekat is called the sanad bazakhiyah, because the lineage is directly from the founder to the Prophet Muhammad without intermediary friends or tabi'in. The founder of the Tijaniyah order was Sheikh Ahmad al-Tijani, he was born in 'Ainul Maadly (name of a Qariyah) in the city of Maghrabil Aqsa (Morocco) in 1150 H. At Ahmad Tijani's meeting with Sheikh Ahmad bin Abdullah al-Hindi, a Sheikh from India in Mecca at the age of 37, he then went to Medina and met Sheikh Muhammad al-Samman, the founder of the Sammaniyah order and from this, according to Azyumardi Azra in his research, that his meeting with Shaykh Samman greatly encouraged Ahmad Tijani to establish the Tijaniyah order. Related to this problem, it is necessary to investigate which in this study is about: “Tawhid Learning Patterns in the Practice of the Tijaniyah Order at Al-Muhajirin-Koba Islamic Boarding School, Bangka Belitung. Related to the problem of the Tijaniyah tarekat, namely: first, how is the pattern of learning monotheism at the Al-Muhjirin Islamic Boarding School in Koba-Bangka Belitung?. Second, how are the forms of amaliyah of the Tijaniyah Order at the Al-Muhajirin-Koba Islamic Boarding School, Bangka Belitung? This research uses descriptive qualitative research. This study aims to describe several things which include the process of entering the Tijaniyah order and the form of monotheism learning and practice in the Tijaniyah congregation, especially at the Al-Muhjirin Islamic Boarding School. From this research, several conclusions were drawn about: learning patterns to convey monotheism material taught at the Muhajirin Islamic Boarding School such as: “the bandongan system or wetonan system, and the sorogan system. But besides that it also uses the halaqah method, lectures, memorization, question and answer and example. Meanwhile, in the practice of the Tijaniyah congregation at the Al-Muhajirin Islamic Boarding School, through the practices or remembrance, namely: reading intentions, common wirid (morning and evening), namely: saying istighfar 100 times, reading the Prophet's prayers 100 times, reading "Laa ilaa hailallah as much as 100 times. Then wirid wazifah consists of: saying istighfar as much as 30 times, reading shalawat fatih as much as 50 times, and reading Jauharatul kamal as much as 12 times. And then read the remembrance of hailallah Friday.